Location Optimization for Square Array Antennas Using Differential Evolution Algorithm - Erkan Afacan (International Journal of Antennas and Propagation)
In recent works thinned arrays giving minimum peak sidelobe levels for planar square antenna arrays are obtained using Hadamard difference sets. In the current work thinned array configurations giving lower peak sidelobe levels than those given in the literature are obtained for square arrays of 6×6, 8×8, 12×12, and 16×16 elements. Differential evolution algorithm is used in the determination of the antenna locations.